Basilar artery plaque distribution is associated with pontine infarction and vertebrobasilar artery geometry - Zheng, Jinmei; Sun, Bin; Lin, Ruolan; Teng, Yongqi; Zheng, Enshuang; Zhao, Xihai; Xue, Yunjing (Frontiers in Neurology, 2023)
Background: Basilar artery (BA) atherosclerosis is a common cause of posterior-circulation ischemic stroke. In this study, we investigate the relationship between BA plaque distribution, pontine infarction (PI) and vertebrobasilar artery (VBA) geometries. Materials and Methods: 303 patients were performed with MRI in this study, patients were divided into three groups: no cerebral infarction (NCI), anterior circulation cerebral infarction (ACCI), and posterior circulation cerebral infarction (PCCI), the VBA geometry was classified into four configurations: walking, tuning fork, lambda, and no confluence. The AP-Mid-BA, Lateral-Mid-BA, and VA-BA angles were measured on three-dimensional time-of-flight magnetic resonance angiography. Patients underwent high-resolution magnetic resonance imaging to evaluate the BA plaque distribution (either anterior, posterior, or lateral wall). Acute and subacute cerebral infarction (including PIs) were identified by T2 weighted imaging-fluid-attenuated inversion recovery and diffusion-weighted imaging. Results: The presence of BA plaque (P < 0.001) and the slices of BA plaque ( P< 0.001) were associated with PCCI. 86 patients all with BA plaque were further analyzed, BA plaques in patients with PI were more frequently located at the posterior wall (50.00%) than at the anterior (10.00%) and lateral (37.50%) walls (P =0.028). Compared with patients without pontine infarction, patients with pontine infarction were more likely to have plaque distributed at the posterior wall (P = 0.009) and have larger VA-BA anger ( 38.72⁰ ± 26.01⁰ vs. 26.59⁰ ± 17.33⁰，P = 0.035) . In the tuning fork group, BA plaques were evenly distributed. BA plaques were more frequently located at the lateral wall than at the anterior and posterior walls in patients with walking, lambda, and no confluence geometry (all P ≤ 0.05). The AP-Mid-BA angle in patients with a tuning fork configuration (14.95⁰ ±11.66⁰) was lower than that in patients with other vascular geometries (P=0.001); there was no significant difference in the VA-BA angle and lateral-mid-BA angle among the four VBA geometries (P >0.05). Conclusion: BA plaque was related to PCCI, BA plaque distribution was associated with PI, and VBA configuration strongly influences BA plaque distribution.